Agroecology and nutritional health: A comparison of agroecological farmers and their neighbors in the Ecuadorian highlands. (May 2021) - Deaconu, Ana; Berti, Peter R.; Cole, Donald C.; Mercille, Geneviève; Batal, Malek
Graphical abstract: Highlights: Agroecological farmers have more nutritious and balanced diets. Agroecology may improve nutrient adequacy through higher production diversity. Agroecology may improve dietary moderation through non-market food consumption. Social and human capital, but not income, may mediate agroecology's diet effects. Agroecological farmers have healthier diets despite spending less money on food. Abstract: Agroecology has received much attention as a sustainable production strategy that may leverage agriculture-nutrition linkages to positively impact farmer nutritional health, but its potential has not been thoroughly established through empirical assessment. This mixed methods study uses survey data from Ecuador to assess how farmers' participation in agroecological associations may impact their diets. Our results suggest that agroecological farmers outperform reference farming neighbors on both nutrient adequacy (i.e. meeting key nutrient needs) and dietary moderation (i.e. avoiding dangerous excesses). Stronger nutrient adequacy is likely related to agroecological farmers' higher production diversity as well as the social and human capital developed within their networks, while stronger dietary moderation is likely related to their greater consumption of foods obtained through own-production and the social economy (e.g. barter). Dietary differences between agroecological and reference farmers occur despite similar incomes and other socioeconomic characteristics, and in fact, agroecological farmers achieve healthier diets while spending less money to purchase foods. Agroecology-based famers' networks may thus hold promise for integrating nutritional health priorities into sustainable food systems.